Leveraging Digital Twin Technology in the Healthcare Industry – A Machine Learning Based Approach - Bende, Aashish; Gochhait, Saikat (International Journal of Psychosocial Rehabilitation, 2020)
This paper deals with the concept of digital twin technology and leveraging the same in the healthcare domain. Digital twin technology is adding value to the healthcare industry by personalizing the diagnosis and therapy selection procedure. Finite Element Analysis (Finite Element Analysis, 2001) is a simulation method used to create a digital replica or a digital instance of the human organs such as the heart, kidney, or brain. IoT devices or sensors such as implantable cardioverter defibrillators or heart pacemakers collect the medical data of patients, which is analyzed to create a virtual instance using simulation software. The virtual instance is continuously updated and is used in generating reports for further diagnosis.